Lupus Means Sacrifices: Perspectives of Adolescents and Young Adults With Systemic Lupus Erythematosus. Issue 6 (26th May 2016) - Tunnicliffe, David J.; Singh‐Grewal, Davinder; Chaitow, Jeffrey; Mackie, Fiona; Manolios, Nicholas; Lin, Ming‐Wei; O'neill, Sean G.; Ralph, Angelique F.; Craig, Jonathan C.; Tong, Allison
Abstract : Objective: Disease activity, organ damage, and treatment burden are often substantial in children and adolescents with systemic lupus erythematous (SLE), and the complex interplay among the developing child, parents, and peers makes effective management difficult. We aimed to describe the experiences and perspectives of adolescents and young adults diagnosed with juvenile‐onset SLE to inform strategies for improving treatment and health outcomes. Methods: Focus groups and face‐to‐face semistructured interviews were conducted with 26 patients ages 14–26 years, from 5 Australian hospitals in 2013–2014. Focus groups and interview transcripts were thematically analyzed. Results: Five themes were identified: marring identity (misrepresented self, heightened self‐consciousness, sense of isolation), restricting major life decisions (narrowed career options, threat to parenthood), multifaceted confusion and uncertainty (frustration at delayed diagnosis or misdiagnosis, needing age and culturally appropriate information, ambiguity about cause of symptoms, prognostic uncertainty, confronting transition to adult care), resentment of long‐term treatment (restricting ambition, animosity toward medication use), and gaining resilience and coping capacities (desire for independence, developing self‐reliance, recalibrating perceived disease severity, depending on family and friends, trusting physicians). Conclusion: Young patients with SLE perceive they have substantially limited physical and social capacities and restricted personal and career goals. Psychosocial and educational interventions targeted at improving confidence, self‐efficacy, disease‐related knowledge, and social support, and at resolving insecurities regarding patients' capacity for self‐management may alleviate psychosocial distress and improve adherence, and thus optimize health outcomes of adolescents and young adults with SLE.